Malaysian public university lecturers’ perceptions and practices of formative and alternative assessment - Sulaiman, Tajularipin; Kotamjani, Sedigheh Shakib; Abdul Rahim, Suzieleez Syrene; Hakim, Muhammad Nazrul (Society for Research and Knowledge Management, 2020)
Successful teaching and learning are highly dependent on assessment as it provides necessary information for making informed decisions in a higher education program. University lecturers should be equipped with skills and knowledge on different methods of evaluation to assess their students effectively. Only few researchers have investigated the assessment methods employed by lecturers in universities in Malaysia. Traditional class-based assessments are the most common mode of assessment although this form of assessment fails to measure students’ learning adequately. This qualitative study aims to determine the level of lecturers’ awareness of the different kinds of assessments at the University Puta Malaysia (UPM). The study sampled 48 lecturers from various faculties at UPM. They responded to a self-reporting questionnaire that required them to indicate their perceived competence in alternative and formative assessments. The result of the thematic analysis revealed that lecturers were utterly aware of formative assessment practices. However, despite the significance of alternative assessments in the learning process, some lecturers were not aware of alternative assessment practices. The implication is